The evolution of money - Orrell, David; Chlupatý, Roman (Columbia University Press, 2016)
The sharing economy's unique customer to company exchange is possible because of the evolution of money. These transactions haven't always been as fluid as they are today, but they are likely to become even more so in the future. It is therefore critical that we learn to appreciate money's elastic nature as deeply as do Uber, Airbnb, Kickstarter, and other leading innovators, and that we better comprehend money's transition from hard currencies to cryptocurrencies, such as Bitcoin, to access their cooperative potential. The Evolution of Money illuminates this fascinating reality, focusing on the tension between currency's real and abstract properties and advancing a vital theory of money rooted in this dual exchange. It begins with the debt tablets of ancient Mesopotamia and follows with the development of coin money in early Greece and Rome, gold-backed currencies in medieval Europe, and monetary economics in Victorian England. The book concludes in the digital era, with the cryptocurrencies and service providers that are making the most of money's virtual aspects and that suggest a tectonic shift within the relevant power structures. By building this organic timeline, The Evolution of Money helps us visualize and strategize money's next, transformative role.